Galaktagogum in Local Vegetables: Habits Revealed by Science - Fadhilah, Nurul; Rahfiludin, Mohammad Zen; Lestantyo, Daru; Winarni, Sri (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Breast milk has an ideal nutritional content for babies according to the needs to grow and develop optimally. Indonesia has a very rich diversity of foodstuffs, one of the habits of the Indonesian people is to regularly consume certain vegetables during breastfeeding. However, some vegetables are not yet popular for breastfeeding mothers to consume even though they contain many benefits such as banana heart, young papaya and spinach. The purpose of this literature review is to provide an evidence-based study on the potential of local vegetables that are commonly consumed during breastfeeding in Indonesia but the content of galaktogogum is not widely known, namely: papaya, spinach, and banana heart. This article is a literature review that discusses the potential of local plants as a source of galactogues. Article search involves 2 databases, namely PUBMED and Google Scholar. The keywords used are: ("Milk, Human"[Mesh]) AND "Galactogogues"[Mesh] AND PAPAYA". ("Milk, Human"[Mesh]) AND "Galactogogues"[Mesh] AND banana flower". ("Milk, Human"[Mesh]) AND "Galactogogues"[Mesh] AND Spinach". ("Milk, Human"[Mesh]) AND "Galactogogues"[Mesh] AND Spinach. Banana hearts, young papayas, and spinach are vegetables that are able to increase breast milk production through galactogue compounds and their derivatives. The saponins contained in the heart of bananas and young papaya can increase the activity of the hormone oxytocin in the myoepithelial cells surrounding the alveolus and ductus. Meanwhile, the phytoestrogen content in spinach can cause biological effects similar to estrogen that are able to increase breast milk production.